The Role of Islam in Strengthening the Family to Countering Radicalism to Support National Resilience in Indonesia - Nafis, Andi Ahmad Zahri; Andi Aderus; Darussalam Syamsuddin; M. Napis Djuaeni (STAIN MAJENE, 2025)
This study aims to examine the role of Islam in strengthening family institutions as the primary bulwark in facing the challenges of dangerous Ideologies, destructive Cultures, and destructive Technologies (ICT), which can undermine Indonesia's national resilience. In the era of globalization, the threats of ICT not only target individuals but also have the potential to disrupt the social, cultural, and spiritual order within families. This research employs a descriptive qualitative approach using library study methods, involving an analysis of verses from the Quran, hadith, and relevant Islamic literature regarding education and family development. The findings indicate that Islam possesses a comprehensive value system in shaping families that are strong spiritually, morally, and socially. If Islamic values are consistently implemented within families, they can cultivate a generation with resilient, religious character, and the ability to withstand the negative influences of ICT. Thus, a strong Islamic family is an important foundation in maintaining social stability and supporting national resilience as a whole.